2019
DOI: 10.3991/ijet.v14i12.10444
|View full text |Cite
|
Sign up to set email alerts
|

The Knowledge Repository Management System Architecture of Digital Knowledge Engineering using Machine Learning to Promote Software Engineering Competencies

Abstract: The knowledge repository management system architecture of digital knowledge engineering using machine learning (KRMS-SWE) to promote software engineering competencies is comprised of four parts, as follows: 1) device service, 2) application service, 3) module service of the KRMS-SWE and 4) machine learning service and storage unit. The knowledge creation, storage, testing and assessing of students’ knowledge in software engineering is carried out using a knowledge verification process with machine learning an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Students can build exceptional game development abilities through the immersive design thinking approach. This is due to the fact that using the Metaverse for the design thinking process can benefit undergraduate students in terms of their ability to develop video games, including by fostering creative problem-solving, enhancing retention and engagement, enhancing collaboration and communication, providing realistic feedback, fostering creativity, enhancing accessibility, and developing technical skills and proficiency [37][38][39][40]. Educators may provide students with creative and efficient learning possibilities by implementing immersive design thinking techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Students can build exceptional game development abilities through the immersive design thinking approach. This is due to the fact that using the Metaverse for the design thinking process can benefit undergraduate students in terms of their ability to develop video games, including by fostering creative problem-solving, enhancing retention and engagement, enhancing collaboration and communication, providing realistic feedback, fostering creativity, enhancing accessibility, and developing technical skills and proficiency [37][38][39][40]. Educators may provide students with creative and efficient learning possibilities by implementing immersive design thinking techniques.…”
Section: Discussionmentioning
confidence: 99%
“…2560-2574 (2017-2031) [30], which has the objectives of an opportunity guarantee of education, equality in education, educational development, educational standards, and employment and income under the context of the Thai and global economies in a society driven by innovative technology and creative thinking as well as wisdom, lifelong learning and a supportive learning environment. This will allow students to perform their own studies, discover information and share knowledge, whereas teachers or experts can use their expertise to pass on knowledge through digital technology [5], [31]- [33].…”
Section: Discussionmentioning
confidence: 99%
“…It is also built as an intelligent interaction system to help answer questions of people wondering whether they are infected with COVID-19 by using information to network and make decisions in the app itself. Which is Thanachawengsakul et al [25] conducted to the knowledge repository management system architecture of digital knowledge engineering using machine learning to promote software engineering competencies research has found that 4 past of component as follow 1) device service, 2) application service, 3) module service of the KRMS-SWE and 4) machine learning service and storage unit. And also, Songsom et al [26] studies system architecture of a student relationship management system using internet of things to collect digital footprint of higher education institutions research has found that 6 past of component as follow 1) service stations, 2) system identification, 3) system integration API, 4) SRM internal system, 5) report analytic and 6) web server and database server.…”
Section: Intelligent Interactive Learning Platformmentioning
confidence: 99%